Characterisation of a fast microcapillary discharge plasma using a compact multi-deflector Thomson parabola ion analyser - LUNNEY, JAMES GERARD (IEEE, 2001)
A compact Thomson parabola ion analyser has been developed and tested on a fast microcapillary plasma discharge. The discharge cell comprises a circular parallel-plate capacitor (1 - 2 nF) with a 50 micron sized hole in the dielectric and a somewhat larger hole in one of the electrodes, which acts to hold off the voltage before self-breakdown in vacuum. The cell capacitance is pulse charged to about lOkV in about 5011s. Selfbreakdown proceeds via a surface discharge over the dielectric exposed in the electrode hole and through the microcapillary in the dielectric. The current in this discharge rises to about 20 kA in 1 ns. The ions in the plasma outflow are predominantly single and doubly charged species from the dielectric and have energies in the range 1-10 keV
PUBLISHED
Keywords: Physics